Analisis asupan karbohidrat dan lemak serta aktivitas fisik terhadap profil lipid darah pada penderita penyakit jantung koroner - Yanti, Novi Dwi; Suryana, Suryana; Fitri, Yulia (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2020)
World Health Organization has estimated that the main cause of death in degenerative diseases is coronary heart disease (CHD). Coronary heart disease can be caused by narrowing of the blood vessels due to high levels of fat in the blood. This is due to excessive intake of fat and carbohydrates, and not doing physical activity or the body is not moving. This study aims to determine the blood lipid profile of outpatients with coronary heart disease. This descriptive-analytic study was used as a case-control study design, with a sample of 64 outpatients. The study was conducted at the Meuraxa Hospital Banda Aceh in March 2019. Intake data were collected using the SQ-FFQ method and physical activity data using the PAL method, while HDL, LDL, and triglyceride data were obtained through secondary data from hospital medical records. The statistical test was used by the Chi-Square test. The results showed that there was an effect of fat intake on blood lipid profiles in coronary heart disease patients (p= 0,006 with OR= 4,80), and the effect of carbohydrate intake (p= 0,032 and OR= 2,96), on the contrary, physical activity (p= 0,130) with a lipid profile showed no association. In conclusion, the intake of fat and carbohydrates has an effect on blood lipid profiles, but physical activity does not affect the blood lipid profiles of patients with coronary heart disease. Suggestions, it is necessary to maintain a balance of consumption of foods that are high in fat, and it is necessary to do consultations regarding low-fat diets